The Role of Financial Management in Supporting Managerial Decision Making - Anita Ardiyanti (ProBisnis : Jurnal Manajemen, 2026)
Financial management plays a strategic role in supporting managerial decision-making within higher education institutions. Effective financial management enables university leaders to allocate resources efficiently, ensure financial sustainability, and improve institutional performance. This study examines the role of financial management in supporting managerial decision-making at Universitas Muhammadiyah Tangerang. Using a descriptive-analytical approach, the research analyzes financial planning, budgeting, reporting, and control mechanisms as key components of financial management. The findings indicate that transparent and accountable financial management provides accurate and timely financial information, which is essential for informed managerial decisions related to academic programs, infrastructure development, and human resource management. Furthermore, effective financial management enhances institutional accountability and supports strategic planning processes. The study concludes that strengthening financial management systems is crucial for improving the quality of managerial decision-making and achieving sustainable institutional development at Universitas Muhammadiyah Tangerang.